Ceritinib versus chemotherapy in patients with ALK-rearranged non-small-cell lung cancer previously given chemotherapy and crizotinib (ASCEND-5): a randomised, controlled, open-label, phase 3 trial. Issue 7 (July 2017) - Shaw, Alice T; Kim, Tae Min; Crinò, Lucio; Gridelli, Cesare; Kiura, Katsuyuki; Liu, Geoffrey; Novello, Silvia; Bearz, Alessandra; Gautschi, Oliver; Mok, Tony; Nishio, Makoto; Scagliotti, Giorgio; et al.
Summary: Background: Ceritinib is a next-generation anaplastic lymphoma kinase (ALK) inhibitor, which has shown robust anti-tumour efficacy, along with intracranial activity, in patients with ALK -rearranged non-small-cell lung cancer. In phase 1 and 2 studies, ceritinib has been shown to be highly active in both ALK inhibitor-naive and ALK inhibitor-pretreated patients who had progressed after chemotherapy (mostly multiple lines). In this study, we compared the efficacy and safety of ceritinib versus single-agent chemotherapy in patients with advanced ALK -rearranged non-small-cell lung cancer who had previously progressed following crizotinib and platinum-based doublet chemotherapy. Methods: In this randomised, controlled, open-label, phase 3 trial, we recruited patients aged at least 18 years with ALK -rearranged stage IIIB or IV non-small-cell lung cancer (with at least one measurable lesion) who had received previous chemotherapy (one or two lines, including a platinum doublet) and crizotinib and had subsequent disease progression, from 99 centres across 20 countries. Other inclusion criteria were a WHO performance status of 0–2, adequate organ function and laboratory test results, a life expectancy of at least 12 weeks, and having recovered from previous anticancer treatment-related toxicities. We randomly allocated patients (1:1; with blocking [block size of four]; stratified by WHO performance status [0 vs 1–2] and presence or absence of brain metastases) to oral ceritinib 750 mg per day fasted (in 21 day treatment cycles) or chemotherapy (intravenous pemetrexed 500 mg/m 2 or docetaxel 75 mg/m 2 [investigator choice], every 21 days). Patients who discontinued chemotherapy because of progressive disease could cross over to the ceritinib group. The primary endpoint was progression-free survival, assessed by a masked independent review committee using Response Evaluation Criteria in Solid Tumors 1.1 in the intention-to-treat population, assessed every 6 weeks until month 18 and every 9 weeks thereafter. This trial is registered withClinicalTrials.gov, numberNCT01828112, and is ongoing but no longer recruiting patients. Findings: Between June 28, 2013, and Nov 2, 2015, we randomly allocated 231 patients; 115 (50%) to ceritinib and 116 (50%) to chemotherapy (40 [34%] to pemetrexed, 73 [63%] to docetaxel, and three [3%] discontinued before receiving treatment). Median follow-up was 16·5 months (IQR 11·5–21·4). Ceritinib showed a significant improvement in median progression-free survival compared with chemotherapy (5·4 months [95% CI 4·1–6·9] for ceritinib vs 1·6 months [1·4–2·8] for chemotherapy; hazard ratio 0·49 [0·36–0·67]; p<0·0001). Serious adverse events were reported in 49 (43%) of 115 patients in the ceritinib group and 36 (32%) of 113 in the chemotherapy group. Treatment-related serious adverse events were similar between groups (13 [11%] in the ceritinib group vs 12 [11%] in the chemotherapy group). The most frequent grade 3–4 adverse events in the ceritinib group were increased alanine aminotransferase concentration (24 [21%] of 115 vs two [2%] of 113 in the chemotherapy group), increased γ glutamyltransferase concentration (24 [21%] vs one [1%]), and increased aspartate aminotransferase concentration (16 [14%] vs one [1%] in the chemotherapy group). Six (5%) of 115 patients in the ceritinib group discontinued because of adverse events compared with eight (7%) of 116 in the chemotherapy group. 15 (13%) of 115 patients in the ceritinib group and five (4%) of 113 in the chemotherapy group died during the treatment period (from the day of the first dose of study treatment to 30 days after the final dose). 13 (87%) of the 15 patients who died in the ceritinib group died because of disease progression and two (13%) died because of an adverse event (one [7%] cerebrovascular accident and one [7%] respiratory failure); neither of these deaths were considered by the investigator to be treatment related. The five (4%) deaths in the chemotherapy group were all due to disease progression. Interpretation: These findings show that patients derive significant clinical benefit from a more potent ALK inhibitor after failure of crizotinib, and establish ceritinib as a more efficacious treatment option compared with chemotherapy in this patient population. Funding: Novartis Pharmaceuticals Corporation.